2014
DOI: 10.17784/mtprehabjournal.2014.12.200
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stretching exercises for posture correction: systematic review.

Abstract: Introduction: Nowadays, postural problems are widely discussed concerns because they involve quality of life and interfere with the functional aspects of individuals. To do this, muscle stretching exercise is suggested as useful in treating postural deviations. Objective: To investigate the effect of muscle stretching on body posture and analyze aspects of prescription and evaluation methods in order to relate the proposed training and results. Method: This systematic review was previously registered and accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…[ 34 ] However, contrary to the results of this study, some review studies have not confirmed the effectiveness of these exercises and programs in patients with neurological disorders. [ 33 35 ] This difference in findings can be related to the heterogeneity of exercise programs and protocols and muscles involved, duration and intensity of training, sample characteristics, effectiveness criteria, type and degree of disability of target group patients, and disease progression in them.…”
Section: Discussionmentioning
confidence: 99%
“…[ 34 ] However, contrary to the results of this study, some review studies have not confirmed the effectiveness of these exercises and programs in patients with neurological disorders. [ 33 35 ] This difference in findings can be related to the heterogeneity of exercise programs and protocols and muscles involved, duration and intensity of training, sample characteristics, effectiveness criteria, type and degree of disability of target group patients, and disease progression in them.…”
Section: Discussionmentioning
confidence: 99%
“…In a 2014 systematic review of 32 studies, Filho et al [39], assessed the effectiveness of stretching for posture correction. Researchers found very little evidence supporting effectiveness in this particular treatment modality [40]. In a 2004 systematic review of 6 studies by Thacker et al [41], researchers sought to determine if stretching has the capability to reduce the risk of a sports injury [35].…”
Section: Joint Manipulation-joint Mobilizationmentioning
confidence: 99%
“…14 Exercise is viewed as an efficient strategy, particularly muscle stretching exercises (MSE), beneficial effects on posture, blood pressure, improved range of motion. [15][16][17][18][19] Also, MSE can minimize muscle fatigue, reduce muscle imbalance, and decrease muscle pain. [20][21][22] Studies have shown that daily exercise over a 10-week duration has demonstrated beneficial benefits in reducing pain in the neck and increasing strength.…”
Section: Introductionmentioning
confidence: 99%